Impact of blood transfusion on outcomes following resection for colorectal liver metastases in the modern era. Issue 7 (1st July 2018) - Pathak, Samir; Al‐Duwaisan, Abdullah; Khoyratty, Fadil; Lodge, J. Peter A.; Toogood, Giles J.; Salib, Emad; Prasad, K. Raj; Miskovic, Danilo
Abstract : Background: Evidence suggests that perioperative blood loss and blood transfusions are associated with poorer long‐term outcomes in patients undergoing other oncological surgery. The aim of this study was to determine the long‐term outcomes of patients requiring a blood transfusion post‐hepatectomy for colorectal liver metastases (CRLM). Methods: This is a retrospective review from 2005 to 2012. Overall survival (OS) and recurrence‐free survival (RFS) were assessed using Kaplan–Meier curves. Red blood cell transfusion (RBCT) and other clinic‐pathological parameters were handled as covariates for Cox regression analysis. Results: Six hundred and ninety patients were included. Median follow‐up was 33 months. Sixty‐four (9.3%) patients required a perioperative RBCT. RBCT was a predictor for decreased OS (median 41 versus 49 months, P = 0.04). However, on multivariate regression analyses preoperative chemotherapy, post‐operative complications and Clinical Risk Score were independently associated with reduced OS, though RBCT was not. There was no association between RBCT and RFS (median 15 versus 17 months, P = 0.28). Conclusions: RBCT is not independently associated with a poorer OS.